Phytochemical Screening and Determination of Total Flavonoid Content of Matoa (Pometia pinnata) Leaf Extract Using UV-Vis Spectrophotometry Method - Damayanti, Fitriani (Makassar Natural Product Journal (MNPJ), 2024)
ABSTRACT Matoa (Pometia pinnata) is a plant belonging to the Sapindaceae family that spreads in the tropical country, including Indonesia. Almost all parts of the plant are utilized by the community including leaves, stem bark, fruit bark and roots which have potential as medicinal plants. Empirically, matoa leaves (Pometia pinnata) can be used as a medicine for fever, skin pain and swollen sprains. Matoa (Pometia pinnata) leaf cooking water can relieve hypertension. Matoa (Pometia pinnata) plants are known to contain flavonoid compounds. Where flavonoid compounds are reported to have antioxidant, antibacterial, antiallergic, antiviral, and anticancer activities. This study aims to determine the phytochemical compound group and determine the flavonoid content of matoa (Pometia pinnata) leaves from the Gowa Regency, South Sulawesi Province. The extract was obtained through maceration method with 96% ethanol solvent. After the thick extract was obtained, phytochemical screening test and determination of flavonoid content by UV-Vis spectrophotometry with quercetin as the standard. Based on the results of this study it can be concluded that matoa leaf extract (Pometia pinnata) contains a class of flavonoids, tanins, saponins, and triterpenoid compounds. Meanwhile, the results of the study showed that the total flavonoid content of matoa leaf extract (Pometia pinnata) at a wavelength of 430 nm was 15,884 mg QE/g extract or 1.588,4%. Keywords : Matoa (Pometia pinnata) Leaf; Extraction; Phytochemical Screening; Flavonoid Content; UV-Vis Spectrophotometry